Biological Effects of Stick Cherry, Soybean Seed and Licorice Root Extracts on Concentration of Serum Hormone Levels in Male Mice - Saleem, Maysoon Mohammad Najeeb Mohammad; Sulaiman, Ghassan Mohammad; Mohammad, Arieg Abdul Wahab; Mohammad, Abbas A (Al-Nahrain Journal of Science, 2014)
Background: This study was carried out to elucidate the effects of the oral administration of three types of herbs extract, stick cherry, soybean seed, and licorice root on concentration of the serum hormone, progesterone, testosterone, and estradiol in albino male mice.Objective: we investigated the impact of biological activity of stick cherry, soybean seed, licorice root extracts on serum concentrations of reproductive hormone as compared with untreated group. Materials and Methods: A total of 48 male mice were used in the experiment. The first group (G1) was the control group which comprised 12 mice treated with 0.5 mL/day distilled water. The remaining 36 mice were divided into (G2), (G3), and (G4). Each group comprised 12 mice. The mice in these groups were orally treated for 21 days with 0.5 mL/day stick cherry ethanol extract, soybean powder hexane extract, or licorice root ethanol extract at concentrations of 10, 10, and 20 mg/kg/day, respectively.Results and Discussions: Results show the effect of stick cherry ethanol extract induced a significant increase in serum concentration of progesterone and testosterone, and a remarkable decrease in estradiol concentration. Soybean extract induced a significant increase in serum concentration of progesterone, testosterone, and estradiol in the treated group compared with the untreated group. No significant effect statistically was found in progesterone, estradiol, and testosterone levels occurred in the group treated with licorice root extract compared with the untreated group.Conclusion: The extracts of stick cherry, and soybean seed exerts a remarkable effect on serum hormone concentration of reproductive organs, progesterone, testosterone and estradiol. Licorice root extract did not show any significant difference for all hormone levels. These extracts might be used as drugs and improve the function of reproductive organ or used as antifertility agents. There is no pharmacological or medical studies have evaluated the effect of stick cherry extract on reproductive hormones in male mice. Meanwhile, limited data and few references are available on the effects of soybean extracts licorice root on the serum hormone levels of reproductive organs.